Race for the exits : The unraveling of Japan's system of social protection - Schoppa, Leonard J. (Cornell University Press, 2006)
This book analyzes the decline of Japan's postwar system of social protection, showing how economic stagnation, demographic shifts, and weakened collective responsibility have led individuals and groups to abandon traditional commitments and undermine the welfare model.